ANALISIS YURIDIS PUTUSAN MAHKAMAH AGUNG NOMOR 981 K/Pdt/2020 TENTANG GUGATAN WANPRESTASI TERHADAP PERJANJIAN HONORARIUM SUCCES FEE - Rafii Fadhil Nasywa; Wardhana, Mahendra (NOVUM : JURNAL HUKUM, 2014)
An agreement is a legally valid act conducted by two or more parties with the intention of establishing a binding relationship that functions as law. Generally, agreements made legally refer to the provisions and requirements set forth in the Indonesian Civil Code. One of the conditions for a valid binding agreement is that the consent must result from free will and without coercion.The objective of this research is to analyze the basis for the judicial considerations in the Surabaya High Court Decision No. 668/Pdt.G/2018/PT.Sby and the Supreme Court Decision No. 981 K/Pdt/2020 concerning breach of contract (wanprestasi) and its implications for the validity of a land sale and purchase agreement that is in dispute. As normative legal research, this study employs a statute approach and a conceptual approach, utilizing primary and secondary legal materials. The research adopts a library research method and employs a qualitative descriptive analysis technique. Based on these methods, the research concludes that a sale and purchase agreement involving a disputed object violates material requirements because it does not align with the principle of good faith. Keywords: Agreement, Default, Court Decision